The p53 miRNA interactome and its potential role in the cancer clinic. (August 2013) - Krell, Jonathan; Frampton, Adam E; Colombo, Teresa; Gall, Tamara MH; De Giorgio, Alex; Harding, Victoria; Stebbing, Justin; Castellano, Leandro
P53 is one of the most frequently mutated tumor suppressors. It regulates protein-coding genes and noncoding RNAs involved in many cellular processes, functioning predominantly at the transcriptional level but also through nontranscriptional processes. miRNAs have recently been identified as key mediators of the p53 stress-response pathway. p53 regulates miRNA transcription and processing, and miRNAs regulate p53 activity and expression and, accordingly, various feedback/feed-forward loops have been identified. Many chemotherapeutic agents induce cancer cell death or senescence via DNA damage and the subsequent activation of p53. Resistance to chemotherapy can occur due to the mutation of components in p53 signaling networks. A better understanding of the role of the various components within these pathways and their interactions with each other may allow the modification and improvement of current treatments, and the design of novel therapies. Improving our knowledge of the role of miRNAs in such p53 signaling networks may be crucial to achieving this.